2016
DOI: 10.1056/nejmoa1507750
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Rosuvastatin in Cardiac Surgery

Abstract: In this trial, perioperative statin therapy did not prevent postoperative atrial fibrillation or perioperative myocardial damage in patients undergoing elective cardiac surgery. Acute kidney injury was more common with rosuvastatin. (Funded by the British Heart Foundation and others; STICS ClinicalTrials.gov number, NCT01573143.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
229
4
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 286 publications
(262 citation statements)
references
References 35 publications
10
229
4
19
Order By: Relevance
“…87 Short-term peri-operative statin therapy increased blood levels of creatinine consistent with acute kidney injury in some randomized trials in cardiac surgery. 273,274 However, in large randomized controlled trials of long-term statinbased therapy, excesses of renal failure were not observed: for example, acute-onchronic renal failure in the SHARP trial among people who already had chronic kidney disease when randomized: 209 (6.7%) cases on simvastatin 20 mg plus ezetimibe 10 mg daily versus 231 (7.4%) cases on placebo (risk ratio 0.91; 95% CI 0.75-1.09); 275 renal failure or impairment in the Heart Protection Study among people with pre-existing cardiovascular disease or diabetes: 65 (0.6%) cases on simvastatin 40mg daily versus 60 (0.6%) cases on placebo (risk ratio 1.07; 95% CI 0.76-1.52); 276 and renal failure in the JUPITER trial in the primary prevention setting: 71 (0.9%) cases on rosuvastatin 20mg daily versus 70 (0.9%) cases on placebo (risk ratio 1.01; 95% CI 0.73-1.41). 246 Consequently, as with differences in the rates of other outcomes that have been associated with statin use in observational studies, the randomized controlled trial evidence does not provide support for an adverse effect of statin therapy on the kidney (except perhaps in the peri-operative setting) and, instead, indicates that it may slow the progression of renal impairment (although the clinical significance of the small effect that has been observed is uncertain).…”
Section: Kidney-related Outcomesmentioning
confidence: 99%
“…87 Short-term peri-operative statin therapy increased blood levels of creatinine consistent with acute kidney injury in some randomized trials in cardiac surgery. 273,274 However, in large randomized controlled trials of long-term statinbased therapy, excesses of renal failure were not observed: for example, acute-onchronic renal failure in the SHARP trial among people who already had chronic kidney disease when randomized: 209 (6.7%) cases on simvastatin 20 mg plus ezetimibe 10 mg daily versus 231 (7.4%) cases on placebo (risk ratio 0.91; 95% CI 0.75-1.09); 275 renal failure or impairment in the Heart Protection Study among people with pre-existing cardiovascular disease or diabetes: 65 (0.6%) cases on simvastatin 40mg daily versus 60 (0.6%) cases on placebo (risk ratio 1.07; 95% CI 0.76-1.52); 276 and renal failure in the JUPITER trial in the primary prevention setting: 71 (0.9%) cases on rosuvastatin 20mg daily versus 70 (0.9%) cases on placebo (risk ratio 1.01; 95% CI 0.73-1.41). 246 Consequently, as with differences in the rates of other outcomes that have been associated with statin use in observational studies, the randomized controlled trial evidence does not provide support for an adverse effect of statin therapy on the kidney (except perhaps in the peri-operative setting) and, instead, indicates that it may slow the progression of renal impairment (although the clinical significance of the small effect that has been observed is uncertain).…”
Section: Kidney-related Outcomesmentioning
confidence: 99%
“…Three recent, high‐quality, randomized clinical trials, including this study's parent trial, have demonstrated that perioperative statin treatment does not reduce postoperative AKI and may, in fact, be harmful 27, 39, 40. The evidence suggests that statins should not be initiated in the perioperative period to reduce AKI.…”
Section: Discussionmentioning
confidence: 87%
“…Leczenie statyną w okresie okołooperacyjnym wydawało się zmniejszać ryzyko pooperacyjnego AF w kilku małych RCT [689,690], ale w kontrolowanej placebo próbie klinicznej, która miała odpowiednią moc statystyczną, nie wykazano wpływu okołooperacyjnego leczenia rosuwastatyną na wystę-powanie AF w okresie pooperacyjnym [691]. Leczenie statyną nie zapobiega również AF w innych sytuacjach klinicznych [692,693].…”
Section: Antyarytmiczne Działanie Leków Nieantyarytmicznychunclassified
“…Mimo początkowych doniesień z metaanaliz [689,932,933] przedoperacyjne leczenie statyną nie zapobiegało AF w okresie pooperacyjnym w prospektywnej, kontrolowanej próbie klinicznej [934]. Inne metody leczenia również oceniano w małych próbach klinicznych generujących nowe hipotezy badawcze, ale nie wykazano jednoznacznie ich korzystnych efektów.…”
Section: Prewencja Migotania Przedsionków W Okresie Pooperacyjnymunclassified